2017
DOI: 10.1371/journal.pone.0169197
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus (HPV) Infection: Molecular Epidemiology, Genotyping, Seroprevalence and Associated Risk Factors among Arab Women in Qatar

Abstract: Human Papillomavirus (HPV) infections are known to cause cervical cancer worldwide, however, limited information is currently available on prevalence, types distribution and risk factors for HPV infection in the Arab countries. We conducted a cross-sectional observational study exclusively of women of Arabic origin residing in Qatar (n = 406) who were selected from the Women’s Hospital at Hamad Medical Corporation (HMC) and Health Centers of the Primary Health Care Corporation in Doha, Qatar over the period Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
19
2
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 32 publications
3
19
2
2
Order By: Relevance
“…In line with our findings, it has been previously reported that HR‐HPV positivity declined with increasing age . Prior studies in KSA and Qatar reported that HPV prevalence was highest among women in the older age groups. Conversely, the HPV positivity rate was highest among women in the younger age groups and decreased with increasing age in Kuwait .…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with our findings, it has been previously reported that HR‐HPV positivity declined with increasing age . Prior studies in KSA and Qatar reported that HPV prevalence was highest among women in the older age groups. Conversely, the HPV positivity rate was highest among women in the younger age groups and decreased with increasing age in Kuwait .…”
Section: Discussionsupporting
confidence: 92%
“…In addition, a subsequent meta‐analysis of women with normal cytological findings found that the adjusted HPV prevalence was 11.7%, although it varies geographically . Furthermore, previous studies in some GCC countries reported HPV prevalence ranging from 2.36% to 60.7% among women with normal cytology, whereas, among women with abnormal cytology, the HPV positivity rate ranged from 16.7% to 64.6% . The high prevalence of HR‐HPV among women with normal cytology in our study could be explained by the low sensitivity of the Papanicolaou test.…”
Section: Discussioncontrasting
confidence: 42%
See 3 more Smart Citations